SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN PEGAWAI BARU DI UNIVERSITAS STIKUBANK (UNISBANK) - , Sunardi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research has developed an application of decision support system as a tool to assist decision makers in making decisions. This system has capability to select new employees, such as academic staff, administrative staff, technician and driver or security guard. The selection process applied in the system refers to the guidance book for recruiting new employees of Unisbank which has 5 stages. The administrative selection uses eligible method, while the psychological test related to field selection and interview are done by applying Fuzzy Inference System (FIS). The final stage is health test in which the system only accepts test results from anamnesis doctors. The results of administrative selection are the participants who passed administrative completeness. FIS results from psychological selection, related field selection and interviews selection are applicantsâ rank. These ranks will be used as basis for decision-makers to determine the passing-grade selection. In the health selection stage the system only produces output only when the applicants join the health test. These results are taken as a recommendation to the leader for recruiting applicant.